Electroacupuncture Alleviates Visceral Hypersensitivity in IBS-D Rats by Inhibiting EGCs Activity through Regulating BDNF/TrkB Signaling Pathway. (14th February 2022) - Zhao, Ying; Jiang, Hui-ling; Shi, Yu; Zhang, Wei; Zhang, Lei-xiao; Hou, Yu-jun; Yang, Zuo-qin; He, Bao-yu; Liang, Fan-rong; Zheng, Qian-hua
Abstract : Objective . To determine whether electroacupuncture (EA) could alleviate visceral hypersensitivity in diarrhea-predominant irritable bowel syndrome (IBS-D) rats by inhibiting EGCs activity via the BDNF/TrkB signaling pathway. Methods . Sprague Dawley rats were randomly divided to a control group ( n = 8) and a model preparation group ( n = 32), which received Senna solution by gavage and CUMS (chronic unpredictable mild stress) for 14 consecutive days and was further divided to a Model group, an EA group (only electroacupuncture), an EA + TrkB agonist group (electroacupuncture and TrkB), and an EA + DMSO group (electroacupuncture and DMSO, n = 8 for each). Rats in the three EA groups were acupunctured at ST25, ST36, and LR3 for 20 min every day for 14 days. Abdominal withdrawal reflex (AWR) was used to quantify visceral sensitivity; reverse transcription polymerase chain reaction (RT-PCR) and double immunofluorescent staining were used to detect the colocalized expression of GFAP/BDNF and GFAP/TrkB. Western Blot (WB) was used to detect the expression of PLC and SP in the colon. Flow cytometry was used to detect the expression of Ca 2+ . Results . EA effectively alleviated visceral hypersensitivity in IBS-D rats (P < 0.05 ). Compared to the control group, the expression of BDNF, TrkB, PLC, SP, and Ca 2+ and the colocalized expression of GFAP/BDNF and GFAP/TrkB increased in the Model group (P < 0.05 ), while all these parameters decreased in the EA group following EA intervention (P < 0.05 ). In addition, no significant difference was found between the EA + TrkB agonist group and the control group (P > 0.05 ). Conclusions . EA alleviates visceral hypersensitivity of IBS-D rats possibly by inhibiting the activity of EGCs through the BDNF/TrkB-PLC-Ca 2+ signaling pathway in the colon.